2002
DOI: 10.1002/hup.388
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and safety aspects of mirtazapine

Abstract: The tolerability and safety profile of the noradrenergic and specific serotonergic antidepressant (NaSSA) mirtazapine reflects its unique pharmacological profile. The 5-HT(2) blocking effect contributes towards its anxiolytic effects and benefits on sleep, as well as preventing the sexual dysfunction that may occur with non-specific stimulation of the serotonin system by drugs such as the selective serotonin reuptake inhibitors (SSRIs). In addition, 5-HT(3) blockade by mirtazapine helps to prevent nausea and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
2
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 17 publications
0
45
2
5
Order By: Relevance
“…Although histaminergic blockage helps to rapid sleep onset, it is assumed that the effects on continuity is due to its 5HT2 and 5HT3 blocking effects (62,63).…”
Section: Mirtazapinementioning
confidence: 99%
“…Although histaminergic blockage helps to rapid sleep onset, it is assumed that the effects on continuity is due to its 5HT2 and 5HT3 blocking effects (62,63).…”
Section: Mirtazapinementioning
confidence: 99%
“…On the other hand, weight gain after antidepressants may override this beneficial effect and induce obesity as an unwanted side effect. Normalization of body weight and unwanted weight gain belong to the benefits and sequelae of treatment with mirtazapine (Nutt, 2002). Leptin morning levels were shown to increase during antidepressive treatment with mirtazapine (Kraus et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It also has anxiolytic and hypnotic properties. Side effects, such as increased appetite, weight gain, dry mouth, and somnolence, are relatively minor complaints (1)(2)(3)(4). Unlike other antidepressants, mirtazapine alone has not been involved as a cause of death by overdose.…”
Section: To the Editormentioning
confidence: 99%
“…Unlike other antidepressants, mirtazapine alone has not been involved as a cause of death by overdose. Numerous studies have shown that Mirtazapine overdose in patients resolves well (1)(2)(3)(4)(5)(6)(7). Therefore, mirtazapine is considered a drug with good tolerability and safety profile.…”
Section: To the Editormentioning
confidence: 99%